Life satisfaction and material well-being of children in the UK - Gundi Knies (University of Essex, Institute for Social and Economic Research (ISER), 2012)
Life satisfaction is increasingly recognised as a desirable individual outcome. Policy attention with respect to child well-being has focused on improving the financial position of families with children. Using Understanding Society I show that child life satisfaction is not associated with household income (poverty), or with a set of new material deprivation measures of child poverty, introduced to help target effective policies that make a real difference to children's lives. Those interested in maximizing society's welfare should shift their attention from an emphasis on increasing consumption opportunities for families with children to an emphasis on increasing social contacts.
Keywords: D01; D31; D61; I14; I30; I31; J13; 330; Life satisfaction; Well-being; Happiness; Child Poverty; Material Deprivation